2016
DOI: 10.3892/or.2016.4743
|View full text |Cite
|
Sign up to set email alerts
|

HOTTIP and HOXA13 are oncogenes associated with gastric cancer progression

Abstract: A long non-coding RNA named HOTTIP (HOXA transcript at the distal tip) coordinates the activation of various 5' HOXA genes which encode master regulators of development through targeting the WDR5/MLL complex. HOTTIP acts as an oncogene in several types of cancers, whereas its biological function in gastric cancer has never been studied. In the present study, we investigated the role of HOTTIP in gastric cancer. We found that HOTTIP was upregulated in gastric cancer cell lines. Knockdown of HOTTIP in gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 45 publications
1
55
0
1
Order By: Relevance
“…Several studies previously demonstrated that HOXA13 and HOTTIP expression are highly correlated. 20,[50][51][52] Specifically, we reported that HOTTIP activates HOXA13 through epigenetic mechanisms including DNA methylation and histone modifications 22 and Wang et al described that, in the Cs12 gastric cells, HOTTIP knockdown attenuates the recruitment of WDR5 and MLL1 and promotes DNMT3B localization on the HOXA13 promoter. 20 Here by analyzing HOXA13 IHC and HOTTIP ISH on consecutive HCC sections, we showed that HOXA13 and HOTTIP displayed intra-tumor heterogeneous pattern of expression and their concomitant overexpression was found in the same populations of transformed hepatocytes.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies previously demonstrated that HOXA13 and HOTTIP expression are highly correlated. 20,[50][51][52] Specifically, we reported that HOTTIP activates HOXA13 through epigenetic mechanisms including DNA methylation and histone modifications 22 and Wang et al described that, in the Cs12 gastric cells, HOTTIP knockdown attenuates the recruitment of WDR5 and MLL1 and promotes DNMT3B localization on the HOXA13 promoter. 20 Here by analyzing HOXA13 IHC and HOTTIP ISH on consecutive HCC sections, we showed that HOXA13 and HOTTIP displayed intra-tumor heterogeneous pattern of expression and their concomitant overexpression was found in the same populations of transformed hepatocytes.…”
Section: Discussionmentioning
confidence: 85%
“…HOTTIP exhibited lymph node metastasis, and the downregulation of HOTTIP impaired GC cell proliferation, promoted cell apoptosis, and reduced cell invasion and migration in GC. 26,27 HOTTIP prevented glioma progression by sponged endogenous miR-101 and inhibited its activity, further F I G U R E 9 The expression levels of three long noncoding RNAs in gastric cancer tissues resulted in increased ZEB1 expression and promoted the process of EMT. 28 In hepatocellular carcinoma, HOTTIP can be negatively regulated by miR-125b, while miR-192/-204-HOTTIP axis may interrupt HCC glutaminolysis through GLS1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that HOTTIP could directly interact with the Trithorax protein WDR5 inducing an open DNA-chromatin configuration to target WDR5/MLL complexes driving histone H3 lysine 4 trimethylation and thus regulating the transcription of 5′end HOXA locus genes [10]. Interestingly, recent studies also found that there is a positive correlation between the expression of HOTTIP and HOX genes in tumors and normal tissue [14, 30–33]. It has demonstrated that HOTTIP was involved in the cancer progression.…”
Section: Discussionmentioning
confidence: 99%